2020
DOI: 10.3390/toxins12030185
|View full text |Cite
|
Sign up to set email alerts
|

Klotho/FGF23 and Wnt Signaling as Important Players in the Comorbidities Associated with Chronic Kidney Disease

Abstract: Fibroblast Growth Factor 23 (FGF23) and Klotho play an essential role in the regulation of mineral metabolism, and both are altered as a consequence of renal failure. FGF23 increases to augment phosphaturia, which prevents phosphate accumulation at the early stages of chronic kidney disease (CKD). This effect of FGF23 requires the presence of Klotho in the renal tubules. However, Klotho expression is reduced as soon as renal function is starting to fail to generate a state of FGF23 resistance. Changes in these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 112 publications
(129 reference statements)
1
36
0
Order By: Relevance
“…Studies have revealed the pleiotropic effect of klotho on bone, the cardiovascular system, and even as a tumour-suppressor molecule [187,234]. Some researchers suggest that (sKL) binds to multiple Wnt ligands, suppressing various gene transcriptions.…”
Section: Klotho Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have revealed the pleiotropic effect of klotho on bone, the cardiovascular system, and even as a tumour-suppressor molecule [187,234]. Some researchers suggest that (sKL) binds to multiple Wnt ligands, suppressing various gene transcriptions.…”
Section: Klotho Proteinmentioning
confidence: 99%
“…Some researchers suggest that (sKL) binds to multiple Wnt ligands, suppressing various gene transcriptions. Increasing klotho regulation stops Wnt activation, which reduces extracellular matrix deposition and cytokine transcription [234]. It seems that klotho deficiency may contribute to the cardiac hypertrophy observed in CKD (stages G3a-b and G4).…”
Section: Klotho Proteinmentioning
confidence: 99%
“…The expression of renal Klotho is decreasing with the progression of kidney injury, where the amount of functional nephrons are reduced and the transfer of phosphate per nephron increased [132]. Interestingly, it has been suggested that the expression of renal Klotho was modulated by phosphaturia and that inhibition of Wnt/ β-catenin signaling prevented the phosphate induced downregulation of Klotho [133,134] Recently, we have examined such a new paradigm and its potential impact on CKD-MBD. We used the unilateral nephrectomy model (UUO), which is ideal to study the rapid development of unilateral renal fibrosis (characterized by induced periostin, decrease BMP7 and Klotho expression) in a non-uremic milieu as the contralateral kidney maintains a normal glomerular filtration [104].…”
Section: New Factors Involved In Ckd-mbdmentioning
confidence: 99%
“…Muñoz-Castañeda et al [ 33 ] further elaborate on the FGF23–Klotho axis, its regulation by the Wnt/β-catenin signaling pathway and vice versa. Starting from their deregulation in CKD, the impact of these axes on pathophysiological processes underlying CKD progression as well as cardiovascular disease and bone disorders are being discussed in detail.…”
Section: Ckd–mbd As a Major Complication In Ckd Affects Cardiovascmentioning
confidence: 99%